SCREENING OF SOME SUGARCANE GENOTYPES FOR GUR*QUALITY - F. Hussain; M. A. Sarwar; A. A. Chattha (Journal of Animal and Plant Sciences, 2007)
A field study to screen five sugarcane genotypes viz; HSF-242, S97-US-127, S97-US-102, S97-US-161 and HSF-240 as standard for their gur quality was conducted at Sugarcane Research Institute Faisalabad during the cropping season 2002-03. Different qualitative parameters of gur including mineral matters%, color, moisture%, net rendements%, acidity, pol% and reducing sugars% were examined. Methods described in Gur Monograph (1951) were followed during experiment. The gur so prepared was stored in gunny bags for a period of ninety days while the analysis of freshly prepared and ninety days old gur was made. The results showed that genotype S97-US-161 produced gur with highest net rendements % and pol% before and after storage. Statistically significant differences were observed with respect to mineral matters%, color, acidity and reducing sugars% while non-significant differences for moisture%, net rendements% and pol% were reported.
Keywords: Sugarcane; genotypes; gur; pol %; reducing sugars %